Upaya Meningkatkan Motivasi Belajar Melalui Penerapan Pendekatan CTL pada siswa di SD 1 Pecangaan kelas 4 - Syailin Nichla Choirin Attalina; Nurul Wakhidah; Rika Izzatun Nikmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve students' motivation and learning outcomes through the application of the Contextual Teaching and Learning (CTL) approach to fourth-grade students of SD 1 Pecangaan. The background of this study is the low motivation and learning outcomes of students in the conventional learning process that does not relate the material to students' real lives. The research method used is the Classroom Action Research (CAR) model of Kemmis and McTaggart which is carried out in two cycles. The instruments used include observation, learning motivation questionnaires, and learning outcome tests (pretest and posttest). The results of the study showed a significant increase in student motivation and learning outcomes after the application of the CTL approach. Students' learning motivation scores increased from the sufficient category (average 62) to high (average 83). Student learning outcomes also increased from an average pretest score of 63 to an average posttest score of 82, with the percentage of learning completion increasing from 35% to 87%. The CTL approach has proven effective because it is able to create active, meaningful, and relevant learning with students' real experiences. Thus, the application of CTL can be used as a strategic solution in improving the quality of learning in elementary schools. Teachers are expected to be able to implement this approach creatively and sustainably so that learning becomes more contextual and enjoyable for students.